The legacy of Vietnam and the Powell doctrine: four case studies - Middup, Luke Foster (2011)
The Vietnam War was one of the most traumatic events ever to afflict the US Military. From the ashes of this defeat, the US Military sought to renew itself. As part of this process of renewal, the US Army in particular engaged in serious soul searching as to how, and under what circumstances, the United States ought to commit itself to war. The answers that were derived from this soul searching are known collectively as the Powell Doctrine, named after General Colin L. Powell, Chairman of the Joint Chiefs of Staff (1989-1993). The elements of the Doctrine are as follows: the need for “overwhelming” force; the need for public and Congressional support; the need for clear objectives; the need for a clear “exit strategy”; and force should only be used in the “vital national interest.”